Characteristic size spectra of cumulus fields observed from satellites - Gifford, Malcolm Douglas, author; Department of Atmospheric Science, Colorado State University, publisher (Colorado State University. Libraries, 1977)
A technique is presented which allows the investigator to monitor size distributions of small scale cumulus fields using satellite data. The limitations of the technique are shown to be the resolution and quality of the satellite imagery. Twenty-four samples of small cumulus are studied using DMSP and SMS-1 satellite imagery. A total of eleven DMSP samples are examined from North Carolina and Florida. These samples are compared to six DMSP samples and seven SMS-1 samples drawn from cumulus fields observed over the subtropical and tropical Atlantic Ocean. Comparisons are based on parameters derived from the least-squares solutions of a linearized first order exponential model. An exponential decrease in cloud number density with increasing cloud diameter is exhibited in both the mean cloud number density distributions of the case studies and the cloud number density distributions of selected typical cumulus samples. The poorer data quality of the SMS-1 imagery is seen to cause deviations from the exponential model in approximately 40% of the samples. The coefficient of exponential decrease in cloud number density is shown to lie in the interval 0.59 to 1.51 km-1. These values are seen to be in excellent agreement with the results of previous investigators. A comparison is made between typical samples of oceanic and continental cloud number density distributions. Although a significant increase in regression slope is seen in the oceanic sample, further research is suggested to bolster current evidence.
November 1977.
Also issued as author's thesis (M.S.) -- Colorado State University, 1977.
Keywords: Cumulus -- Remote sensing